A Study on the Overseas Communication of Joy of Life and the Cultural Export of Chinese Online Literature in the Context of Globalization - Lin, Haoyu (Art and Society, 2026)
This study examines the overseas communication of Joy of Life and its role in the cultural export of Chinese online literature within the context of globalization. Drawing on media analysis, industrial reports, and audience reception data, the research explores how Chinese web literature and its adaptations contribute to the international circulation of cultural narratives. The paper discusses the development of Chinese online literature, its distinctive features, and the ways in which Joy of Life engages global audiences through streaming platforms and translation networks. It analyzes how cultural translation and localization strategies allow traditional Chinese values and historical imagination to be interpreted in different cultural settings. The study also considers the ideological dimensions of the series, showing how Confucian ethics, moral reflection, and aesthetic presentation support China’s cultural soft power. Furthermore, it examines the media industry networks and policy frameworks that facilitate global dissemination, emphasizing cooperation between state policy, creative industries, and digital platforms. The research concludes by identifying future directions for the globalization of Chinese online literature, highlighting the need for balance between cultural authenticity and international accessibility. Overall, the paper offers a comprehensive view of how Chinese digital narratives participate in global cultural exchange and how Joy of Life represents a new model of cultural communication in the digital era.